The structural relaxation and anisotropy of the spring-back in metals - Usov, V.V.; Novikov, V.V.; Shkaratulyak, N.M.; Titenkov, A.N.; Mamay, D.V. (Functional Materials, 2007)
The spring-back phenomenon in rolled copper and aluminum sheets has been studied in expirement. The time dependences of strain at bending of specimens under permanent load have been described by power functions with a fractional index. The anisotropy of the spring-back phenomenon has been on fractal concepts of the relaxation processes under external permanent stress.